Design and examination of the new biosoluble casting alloy of the system Mg–Zr–Nd for osteosynthesis - Shalomeev, Vadim; Aikin, Nikita; Chorniy, Vadim; Naumik, Valeriy (Eastern-European Journal of Enterprise Technologies, 2019)
We have performed a comparative analysis of existing materials for the fabrication of implants and report their physical-mechanical properties; their advantages and disadvantages have been defined. It is shown that magnesium alloys are among the most promising biosoluble materials. They are bioinert and biocompatible, but their use in osteosynthesis is limited mainly by their inadequate mechanical properties due to the high rate of biodegradation, which requires improving them by changing the chemical composition of the alloy. In order to develop a new magnesium-based biosoluble alloy, we have selected the most suitable doping systems in accordance with the established criteria. Employing the methods of experiment design, we studied the separate and joint influence of zirconium, neodymium and zinc on structure formation and mechanical properties of magnesium alloy. Mathematical models have been constructed that describe the influence of the examined alloying elements on the mechanical properties of the metal. Using the regression equations derived, we have carried out the optimization of the chemical composition of magnesium alloy. The industrial and pre-clinical tests of implants made from the designed biosoluble alloy have been performed. Experiments on animals confirmed the absence of toxic effect from the products of degradation of the devised magnesium alloy on a living organism. Studying the influence of the designed alloy on reparative osteogenesis during experiment on rabbits has shown the positive dynamics of bone tissue regeneration without noticeable changes in its structure, which ensures reliable merging of elements in bones at osteosynthesis. It was established that the implants made from the designed alloy possess the necessary level of mechanical properties that match the mechanical properties of bone tissue. At the same time, they are non-toxic and provides a secure bone tissue healing until the complete fracture consolidation. Positive results of the experiments conducted allow us to suggest a favorable prognosis on the possibility of using implants made from the devised biosoluble alloy of the system Mg–Zr–Nd in humans